Attachment and Social Connectedness: The Sequential Mediating Role of Inferiority and Perfectionism - Ezgi Ekin Şahin; Baki Duy (International Journal of Emotional Education, 2023)
A large body of research has been reported on the lifelong consequences of attachment, with social connectedness being one of the main related factors. It is thus crucial to determine the mediating variables in the relationship between attachment and social connectedness. To better understand the relationship between anxious and avoidant attachment styles and social connectedness among university students, this study investigated the sequential mediating roles of inferiority and perfectionism. The study involved 390 undergraduate students (257 female, 133 male) enrolled in various undergraduate programs. Data was collected through various scales including the Experiences in Close Relationships, Almost Perfect Scale, Social Connectedness, and Inferiority Scale. Structural equation modeling shows that adaptive perfectionism partially mediates the relationship between avoidant attachment and social connectedness. Additionally, inferiority functions as a mediator between anxious attachment and maladaptive perfectionism, while maladaptive perfectionism partially functions as a mediator between inferiority and social connection. The results suggest that it would be beneficial for practitioners to address inferiority and perfectionism so as to promote social connectedness among undergraduate students.